Systematic Risk, Hedging Pressure, and Risk Premiums in Futures Markets - Bessembinder, Hendrik (Review of Financial Studies, 1992)
I examine the uniformity of risk pricing in futures and asset markets. Tests against a general alternative do not reject complete integration of futures and asset markets. As predicted, estimates of the “zero-beta” rate for futures are close to zero, and premiums for systematic risk do not differ significantly across assets and futures. There is, however, evidence consistent with a specific alternative model presented by Hirshleifer (1988). Returns in foreign currency and agricultural futures vary with the net holdings of hedgers, after controlling for systematic risk. These results imply a degree of market segmentation and support hedging pressure as a determinant of futures premiums.